2018
DOI: 10.2169/internalmedicine.9382-17
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transhepatic Self-expanding Metallic Stent Placement for the Treatment of Malignant Afferent Loop Obstruction

Abstract: We report the case of a 71-year-old man with afferent loop obstruction (ALO) after Roux-en-Y reconstruction due to gastric cancer. Computed tomography showed a distended afferent loop and a dilatated bile duct. We could not reach the stricture site in the afferent loop using a gastroscope. We performed percutaneous transhepatic biliary drainage (PTBD) and placed a self-expanding metallic stent (SEMS) in the duodenal stricture through the PTBD route. Although an endoscopic approach is preferable, when PTBD can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Bleeding and sepsis have been reported as complications after a PD reoperation. 15 The percutaneous approach is less invasive than open surgery and has been shown to provide effective palliation; 16 , 17 , 18 , 19 however, it is difficult to perform percutaneous transhepatic biliary drainage (PTBD) in patients without intrahepatic bile duct dilation or patients with ascites. PTBD includes causes severe adverse events, such as bleeding, biliary peritonitis, acute cholangitis, frequent catheter dislodgement, and poor quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding and sepsis have been reported as complications after a PD reoperation. 15 The percutaneous approach is less invasive than open surgery and has been shown to provide effective palliation; 16 , 17 , 18 , 19 however, it is difficult to perform percutaneous transhepatic biliary drainage (PTBD) in patients without intrahepatic bile duct dilation or patients with ascites. PTBD includes causes severe adverse events, such as bleeding, biliary peritonitis, acute cholangitis, frequent catheter dislodgement, and poor quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that transhepatic stent placement is an effective treatment for recurrent malignant obstruction in patients with altered bowel anatomy. The technical feasibility of this procedure has been suggested in a few prior studies, including 10 or fewer cases [ 6 7 8 ]. However, to date, its application has been limited to afferent loop obstruction after Billroth II reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…In such patients, the percutaneous transhepatic approach has been used as an alternative technique for successful stent placement [ 6 7 8 ]. However, clinical experiences with transhepatic enteral stent placement have been limited to small case series including less than 10 patients [ 6 7 ]. In addition, prior studies [ 6 7 8 ] exclusively addressed afferent loop obstruction after Billroth II reconstruction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Various etiologies of ALO have been reported, and the treatment differs between malignant and benign etiologies. For patients in whom this syndrome is due to malignant obstruction, less invasive, nonsurgical therapy, such as percutaneous transhepatic biliary drainage (PTBD), percutaneous transhepatic duodenal drainage (PTDD), [25] direct percutaneous tube duodenal enterostomy [6] or self-expanding metal stents placement in afferent loop [7,8] is preferred because these patients are in poor condition due to the advanced stage of their malignancy. On the contrary, for patients with benign obstruction, surgical intervention including adhesiolysis, [7] jejunojejunostomy with Braun procedure or Roux-en-Y conversion have been recommended as the choice.…”
Section: Introductionmentioning
confidence: 99%